قيمة الإثبات بالدليل الكتابي في الفقه الإسلامي والقانون الجزائري - عبدالله، شهرزاد; بن صافى، حبيب Bin Safi, Habib (جامعة الجيلالي ليابس سيدي بلعباس - مخبر البحوث والدراسات الاستشراقية فى حضارة المغرب الإٍسلامى, 2020)
The written evidence at the top of the pyramid of evidence at all, because of the confidence and stability may not provide the rest of the evidence that can be affected by many factors that weaken the strength of the evidence, and perhaps this importance derived from the words of the words of God Almighty in his book : "O ye who believe, if you call a religion for a specified term, write it ..."bakara 181/182 This importance has not been negated by the statutes of law, especially the Algerian law. It has been agreed in its entirety that the written evidence is absolutely authoritative, because it constitutes a burden of proof in practice, whether in the form of official editors. To the conditions established by law, or customary editors to be released by the stakeholders among themselves.
لقواعد الإثبات أهمية بالغة الأثر لدى العاملين بالقانون والمتقاضين، باعتبار الدليل هو قوام حياة الحق ومعقد النفع منه، والحق يتجرد من قيمته مالم يقم الدليل على الحادث المبدئ له سواء تصرف قانوني كان أو حادث مادي، وإذا كانت هذه هي أهمية قانون الإثبات بشكل عام. فوجب بيان ما يتمتع به الدليل الكتابي من أهمية فهو وسيلة من وسائل المعرفة. ومدى اعتباره كأداة من أدوات حفظ ما تضمنه من حقوق والتزامات.
Keywords: الإثبات الجنائي -- التشريعات الجزائرية -- الفقه الإسلامي -- المجتمعات المدنية